2019
DOI: 10.1111/exsy.12405
|View full text |Cite
|
Sign up to set email alerts
|

Automatic assignment of reviewers in an online peer assessment task based on social interactions

Abstract: Online peer assessment tasks are very popular and have unique characteristics that improve learning and encourage social interactions in a distance education environment. Unfortunately, social factors have usually been ignored in the process of selecting reviewers for online peer assessment tasks. We hypothesise that this fact could have some influence on the lack of engagement and participation by some learners. For this reason, we propose an approach in which social network analysis techniques, expert criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…At the individual user level we have proposed the following metrics, which were explained in depth in our previous research (Anaya et al, 2019): the number of conversations that a student has started (Initiative); the number of messages that a student has sent (Messages); the number of replies to messages sent by a student (Popularity); Closeness centrality (Closeness); Betweenness centrality (Betweeness); Eigenvector centrality (Eigenvector).…”
Section: Student Social Behavior Attributes and The Social Network An...mentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual user level we have proposed the following metrics, which were explained in depth in our previous research (Anaya et al, 2019): the number of conversations that a student has started (Initiative); the number of messages that a student has sent (Messages); the number of replies to messages sent by a student (Popularity); Closeness centrality (Closeness); Betweenness centrality (Betweeness); Eigenvector centrality (Eigenvector).…”
Section: Student Social Behavior Attributes and The Social Network An...mentioning
confidence: 99%
“…To have a full implementation of the ID, we need to elicit the numerical values corresponding to the probability and utility parameters. By refining the scheme of elicitation used by (Anaya et al, 2019), we propose a more sophisticated approach by partitioning the set of numerical parameters into three sets: 1. Those parameters that are taken from expert knowledge and that do not depend on the course to which the model is applied.…”
Section: Numerical Parametersmentioning
confidence: 99%
“…In the selection rules for the review of learners' work, it is possible to consider adding a mandatory assignment selection method, or to combine the mode of learners' arbitrary choice of assignment and the mode of the system to automatically push assignments. In the current online peer assessment, there are mainly two selection rules for the review of learners' work: one is that learners choose the work to review according to their own preferences, and the other is assignment assigned by the system (Anaya et al, 2019). Since participation behaviour positively and significantly affects learners' social network prestige, combined with directional research in social network characteristics, it can be inferred that learners who submit assignments late and with poor quality have difficulty getting more feedback to help them reflect, especially from a high-prestige group.…”
Section: Implications For Education and Practicementioning
confidence: 99%
“…Students in the study by Alkhalifa and Devlin (2021) revealed this, clarifying that suitable pairing in peer assessment could increase their engagement. Anaya et al (2019) and Capuano and Caballé (2015) observed that many studies ignore the selection of reviewers in peer assessment, as reviewers are determined randomly or manually by experts. Random or manual matching is not viable, especially in online environments which involve a large number of students.…”
Section: Introductionmentioning
confidence: 99%
“…Random or manual matching is not viable, especially in online environments which involve a large number of students. Moreover, the social interactions of peer assessments (e.g., characteristics of peers) have still not been addressed in depth (Anaya et al, 2019;van Gennip et al, 2009), despite the fact that social interactions between peers play an important role in peer assessment (Bouguessa & Romdhane, 2015). Thus, this study examined such issues in the context of addressing authors' doubts about the value of the feedback received in peer assessment.…”
Section: Introductionmentioning
confidence: 99%